Principles of modeling process of production of sugar beet - Волоха, М. П. (Problems of Environmental Biotechnology, 2013)
This paper is devoted to the features modeling of technological processes of production of sugar beet, the overview of the literature is presented,  and characteristic features of sugar beet production are marked out. On the basis of the carried-out analysis the basic principles of modeling technological processes of production and processing of sugar beet were offered.